2016
DOI: 10.1371/journal.pbio.1002424
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Cortical Oscillations by Low-Frequency Direct Cortical Stimulation Is State-Dependent

Abstract: Cortical oscillations play a fundamental role in organizing large-scale functional brain networks. Noninvasive brain stimulation with temporally patterned waveforms such as repetitive transcranial magnetic stimulation (rTMS) and transcranial alternating current stimulation (tACS) have been proposed to modulate these oscillations. Thus, these stimulation modalities represent promising new approaches for the treatment of psychiatric illnesses in which these oscillations are impaired. However, the mechanism by wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
171
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(185 citation statements)
references
References 62 publications
(69 reference statements)
12
171
2
Order By: Relevance
“…Since we also applied 20 Hz tACS, but at rest, it is possible that this frequency band is primarily effective when background activity is modulated (by task activation) and not at rest. Indeed, previous study found brainstate dependent effects of tACS (Feurra et al, 2013; Neuling et al, 2013; Alagapan et al, 2016; Ruhnau et al, 2016). Therefore, it might be interesting to alter the task context to see whether effects of tACS are context-dependent and differ from effects of tACS on resting IHI.…”
Section: Discussionmentioning
confidence: 93%
“…Since we also applied 20 Hz tACS, but at rest, it is possible that this frequency band is primarily effective when background activity is modulated (by task activation) and not at rest. Indeed, previous study found brainstate dependent effects of tACS (Feurra et al, 2013; Neuling et al, 2013; Alagapan et al, 2016; Ruhnau et al, 2016). Therefore, it might be interesting to alter the task context to see whether effects of tACS are context-dependent and differ from effects of tACS on resting IHI.…”
Section: Discussionmentioning
confidence: 93%
“…However, they focused on alpha activity during wakefulness and a different mechanism might hold true for sleep. A recent report from our group [53] showed stimulation effects that outlast stimulation depended on the specific state in wakefulness. Moreover, using a computational model, the study suggested that recurrent connections in thalamo-cortical and cortico-cortical loops led to outlasting effects of stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Novel brain stimulation tools such as rTMS [5], tACS [18] or direct cortical stimulation [125] allow entraining distinct spectral signatures to subsequently study cross-frequency interactions. Using this approach, it has been demonstrated that both alpha and gamma oscillations might drive CFC interactions, which allows for true bidirectional information integration across temporal scales [78].…”
Section: Figurementioning
confidence: 99%